YAŞLANMA VE MEKÂN İLİŞKİSİ ÜZERİNE: TÜRKİYE'DE YAŞLI ERKEK BİREYLERİN CAMİİ VE KAHVEHANE KULLANIMLARININ ANALİZİ - Sağman, Mahmud Mücahid; Esendemir, Şerif (Bursa Teknik Üniversitesi, 2019)
Yaşlanma ve yaşlılık üzerine Türkiye'de akademik anlamda çalışmalar yeni yeni artmakta ve çeşitlenmektedir. Genç nüfusa sahip olan Müslüman dünya yaşlanmayla ortaya çıkan “toplumsal durum”u henüz tam anlamıyla analiz edebiliyor mu? Modernleşmeyle hemhal olan bir ülke de “yaşlılığın” çözüm bekleyen sorun veya toplumsal belirleyen olarak ortaya çıkacağı kaçınılmazdır. Modernizm sonrasında ortaya çıkan konfor, bireysellik gibi tartışma alanları aslında Batı toplumunda gençlik çalışmalarını fazlasıyla tetiklemiştir. Genç nüfus araştırmaları sanayi toplumlarında nüfusun yaşlılığa doğru seyrine işaret ediyordu, fakat sonuçlarına bakıldığında yaşlanan her toplumun bireyleri aynı toplumsal durumla yüzleşmek zorunda mı?Türkiye, TÜİK verilerine göre 2030'dan itibaren yaşlı nüfusun baskın olduğu bir ülke olacak. Tüm organize yapılar birçok faaliyetini artık onları da hesaba katarak yapmak zorunda olacaklar. Bizim çalışmamızın asli vurgusu yaşlanma ile ortaya çıkan toplumsal durumu mekân ilişkisi üzerinden analiz etme üzerinedir. Cami ve kahvehane gibi Türkiye toplumunun göz önünde olan baskın iki mekânın yaşlılar tarafından neden tercih edildiği analiz edilmiştir.

Academic studies on aging and elderliness in Turkey has been increasing and diversifying recently. Does the Muslim world, which has a younger population than the West, able to analyze “the social situation “that emerged with aging fully? It is inevitable that old age/elderliness will emerge as an unresolved issue or a social determinant in a country like Turkey which has a relation with modernization in its last century. The matters of debate such as comfort, individuality which have emerged in the wake of modernism, have, in fact, triggered studies on youngness in Western society at the same time. All young population surveys indicated the decline in marriages the disintegration of the family, and the progression of the growing population towards old age in the industrial societies, but in terms of their results, do the elderly individuals of each aging community have to face the same social situation with the same level of experience?Turkey, according to TUIK data from 2030 will became a country where the elderly population is dominant. All organized structures will have to do many of their activities by taking this issue into account. The main emphasis of our study is on analyzing the social situation that emerged by aging through the relation of space. The reason why the two dominant places like mosque and coffehouse were preferred by the elderly people were analyzed
ON AGING AND SPACE RELATİONSHİP: ANALYSIS OF MOSQUE AND COFFEE SHOPS IN INDIVIDUAL USE OF ELDERLY MEN IN TURKEY
Keywords: Sociology; Sosyoloji